2018
DOI: 10.1159/000493765
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Sum Analysis of the Learning Curve for Modified Retroperitoneoscopic Living-Donor Nephrectomy

Abstract: Objectives: To introduce our modified retroperitoneoscopic living-donor nephrectomy (RPLDN) techniques and estimate the learning curve. Methods: We retrospectively evaluated 121 consecutive donors who underwent modified RPLDN performed by a single surgeon. While the surgeon controlled the renal vessels, one hand was inserted through an abdominal incision for assistance. The kidney was manually retrieved through the abdominal incision. The learning curve was evaluated using the cumulative sum (CUSUM) method, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…21 The CUSUM model demonstrated an initial learning phase for HARPLDN of 32 cases by a urologist who had performed 1000 retroperitoneoscopic procedures. 22 There is little evidence regarding the learning curve for RALDN. A randomized controlled trial showed that among surgeons familiar with LDN, transitioning to the robotic-assisted approach appears to have a relatively steep learning curve of 20 cases based on a comparison of the LDN and RALDN procedures.…”
Section: Discussionmentioning
confidence: 99%
“…21 The CUSUM model demonstrated an initial learning phase for HARPLDN of 32 cases by a urologist who had performed 1000 retroperitoneoscopic procedures. 22 There is little evidence regarding the learning curve for RALDN. A randomized controlled trial showed that among surgeons familiar with LDN, transitioning to the robotic-assisted approach appears to have a relatively steep learning curve of 20 cases based on a comparison of the LDN and RALDN procedures.…”
Section: Discussionmentioning
confidence: 99%